The complete mitochondrial genome of Cherskii's sculpin (Cottus czerskii) (Scorpaeniformes: Cottidae). (3rd July 2016) - Han, Xiaomin; Li, Cheng; Zhao, Shuai; Xu, Chunzhu
Abstract: The complete mitogenome sequence of Cherskii's sculpin ( Cottus czerskii ) is determined using long PCR. The genome is 16, 534 bp in length and contains 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and a control region. The overall base composition of the heavy strand is A (26.4%), C (30.1%), T (26.1%) and G (17.5%). The control region is 857 bp in length and the A + T content of the region is 61.5%. The extended termination-associated sequence domain, the central conserved domain and the conserved sequence block domain are defined in the mitochondrial genome control region of Cherskii's sculpin. Mitochondrial genome analyses based on MP, NJ and Bayesian analyses yielded identical phylogenetic trees, indicating a close phylogenetic affinity of the 21 Actinopterygii species. It appears that no less than two major phyletic lineages were present in Actinopterygii. The main clades within the Perciformes and Scorpaeniformes supported are: a clade including the Scombridae, Kyphosidae and Percichthyidae; a clade (Cottidae) with the Trichodontidae as the sister taxon to Pholidae, Anarhichadidae and Zoarcidae, which was supported by bootstrap values of 92%. The five Cottus species formed a paraphyletic group with the high bootstrap value (100%) in all examinations.